MEMBANGUN KEBENARAN TENTATIF DALAM DISIPLIN AKUNTANSI (TAFSIR DAN KRITIK ATAS KUASA RELATIVITAS KEBENARAN) - Sulistiyo, Agung Budi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
This paper attempts to explain that there is the power of relativity of truth in developing the â€œcurrentâ€ knowledge, no exception in accounting discipline. The context of â€œcurrentâ€ cannot be separated from the element of time and space where we interact in it. The result of social interaction and the capture of phenomenas is what underlies this paper.Â The concept of the relativity of thruth to be an axiom that should not be interfered with so that when anyone whom disputed it will be considered intorelant, selfish and small-minded. If we explore this concept in depth, actually the concept will bring us to the paradoxical attitude (double-standard of attitude) and ambivalent (double-standard of truth) in every process of our thought.